New Man – New Creation in the Theology of Paul - Paul Sciberras (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2019)
God had congratulated himself for creating the universe and humankind (Gen 1,31), a “very good” creation brought to nought by human sin. However, human nature still sighs and longs for the goodness and image of God within. God’s creation yearns to be created anew. Paul’s understanding of “new creation” and “new man” looks to the wise plan of God negated by sin. For Paul, the new era, in which the new creation reaches its aim in perfection, is the time of the parousia, the new and future coming of Jesus Christ. The Apostle of the Gentiles understood “kainē ktisis” in a soterio-cosmological sense, as the event consequent upon the redemption brought about by Christ Jesus that will be fulfilled in the parousia. New creation, new mankind in a new covenant takes place in communion with the death and resurrection of Christ Jesus in Baptism. The fundamental condition by which the revelation of the mystery of God takes place is the new covenant fulfilled in the blood of Christ and its effects: the outpouring of the Holy Spirit, upon those who believe, as even the prophets had foretold. One can observe the development of the Pauline thought in his Letters: from a theological perspective and its legitimacy in the Major Letters, to the practical consequences in the daily life of the Christian assemblies in the Deutero-Pauline Letters, that emerge from the application of these theological arguments.